What a patient needs to know about the virus human papillomas and cervical cancer? - Sergei P. Sinchikhin; Lusine V. Stepanyan (IP Berlin A.V., 2021)
According to experts of the World Health Organization, cervical cancer is the only cancer that can be completely prevented through the introduction of mass screening and educational information in the population. One of the activities of the obstetrician-gynecologist is the conduct of health education. However, for a variety of reasons, a practical doctor may have difficulty preparing for informational and educational meetings with patients. Aim. To prepare a clinical lecture for the obstetrician-gynecologist, which can be used in educational work with the population on the prevention of human papillomavirus infection and cervical cancer. Materials and methods. The information material includes data from foreign and domestic scientific articles available at PubMed on this topic and published over the past 10 years. Results. A systematic analysis of the data contained in the modern literature on human papillomavirus, human papillomavirus infection and cervical cancer has been carried out. Information is presented on the prevalence of diseases, diagnostic methods, and features of the course of human papillomavirus infection, the role of human papillomavirus in the development of cervical cancer. Attention is drawn to the importance of preventive examinations. Part of the information is presented in the form of answers to patients questions, which makes the information presented especially memorable. Conclusion. It is hoped that the prepared lecture will be useful for the educational work of the obstetrician-gynecologist and will increase the educational information of the population on the prevention of cervical cancer.